2013
DOI: 10.1021/cn400100f
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Bexarotene Treatment Rescues Dopamine Neurons and Restores Behavioral Function in Models of Parkinson’s Disease

Abstract: Nurr1 is a nuclear hormone receptor (NucHR) strongly implicated in the growth, maintenance, and survival of dopaminergic neurons. Nurr1 may be unable to bind ligands directly, but it forms heterodimers with other NucHRs that do. Using bioluminescence resonance energy transfer (BRET) assays to directly monitor interactions of Nurr1 with other NucHRs, we found the cancer drug bexarotene (Targretin, also LGD1069) displayed biased interactions with Nurr1-RXR heterodimers compared with RXR-RXR homodimers. Remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
111
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 32 publications
1
111
0
3
Order By: Relevance
“…The effect of reducing soluble Aβ levels has been confirmed by several studies, although the reduction of Aβ plaques by Targretin remains controversial. Targretin also acts to prevent loss of dopaminergic neurons and restore behavioral function in rodent models of Parkinson's disease [54] , and it relieved positive symptoms of schizophrenia in a randomized, double-blind, placebo-controlled multicenter trial [55] . Thus, RXRα-selective modulators are a class of very promising drug candidates for cancer, metabolic syndromes, and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of reducing soluble Aβ levels has been confirmed by several studies, although the reduction of Aβ plaques by Targretin remains controversial. Targretin also acts to prevent loss of dopaminergic neurons and restore behavioral function in rodent models of Parkinson's disease [54] , and it relieved positive symptoms of schizophrenia in a randomized, double-blind, placebo-controlled multicenter trial [55] . Thus, RXRα-selective modulators are a class of very promising drug candidates for cancer, metabolic syndromes, and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Volakakis et al recently showed that bexarotene could induce expression of a subset of Nurr1 target genes, including the GDNF receptor kinase Ret (19). However, unlike the McFarland et al study (18), bexarotene failed to protect 6-OHDA-lesioned rats (19), highlighting the importance of developing more potent Nurr1:RXR heterodimer ligands. Thus, Spathis et al (6) attempted to develop novel and specific Nurr1:RXRα activators by synthesizing a series of compounds optimized using in silico docking simulations, and testing their effectiveness using a variety of assays.…”
mentioning
confidence: 97%
“…Based on these findings, a potential approach to enhance Nurr1's function in PD is to activate Nurr1:RXRα heterodimers using RXR ligands. Indeed, a recent study by McFarland et al (18) demonstrated that a synthetic RXR ligand, bexarotene (a cancer drug under the name Targretin), successfully activated Nurr1's function by inducing expression of DA-specific genes, rescued mDA neurons, and reversed behavioral deficits in 6-hydroxydopamine (6-OHDA)-lesioned rats. It is important to note that in that study, bexarotene's effective concentration was 100-fold lower than that used in rodent cancer models (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two such ligands, XCT0135908 and bexarotene (14,16), have been shown to activate Nurr1:RXRα as well as other RXRα heterodimers. Bexarotene, an approved antineoplastic agent activates RXRα heterodimers with liver X receptor (LXR), peroxisome proliferator-activated receptor gamma (PPARγ), and Nurr1, has shown promising results in animal models of Alzheimer's disease and PD (16,17), but these results have not been replicated (18,19). In vitro, XCT0135908 (14) activates Nurr1:RXRα heterodimers and RXRα:RXRα homodimers (17), but its bioavailability is unknown.…”
mentioning
confidence: 99%